2021
DOI: 10.3389/fneur.2021.777845
|View full text |Cite
|
Sign up to set email alerts
|

Resective, Ablative and Radiosurgical Interventions for Drug Resistant Mesial Temporal Lobe Epilepsy: A Systematic Review and Meta-Analysis of Outcomes

Abstract: Objectives: One-third of individuals with focal epilepsy do not achieve seizure freedom despite best medical therapy. Mesial temporal lobe epilepsy (MTLE) is the most common form of drug resistant focal epilepsy. Surgery may lead to long-term seizure remission if the epileptogenic zone can be defined and safely removed or disconnected. We compare published outcomes following open surgical techniques, radiosurgery (SRS), laser interstitial thermal therapy (LITT) and radiofrequency ablation (RF-TC).Methods: PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…Additionally, the resection of at least 27% of the PiC was associated with a high rate (79%) of seizure freedom in long‐term FU. These findings are in line with previously reported series on patients with mTLE following tsSAHE 10,16 . In the present study, we for the first time show that an extent of PiC resection above 27% of PiC volume is the only independent significant predictor for reduction or withdrawal of AEDs during the long‐term FU following tsSAHE.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, the resection of at least 27% of the PiC was associated with a high rate (79%) of seizure freedom in long‐term FU. These findings are in line with previously reported series on patients with mTLE following tsSAHE 10,16 . In the present study, we for the first time show that an extent of PiC resection above 27% of PiC volume is the only independent significant predictor for reduction or withdrawal of AEDs during the long‐term FU following tsSAHE.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with previously reported series on patients with mTLE following tsSAHE. 10,16 In the present study, we for the first time show that an extent of PiC resection above 27% of PiC volume is the only independent significant predictor for reduction or withdrawal of AEDs during the longterm FU following tsSAHE. The analysis of further Values indicated in mL.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…A single-center study including pediatric patients with drug-resistant lesional epilepsy showed that Engel class I outcome was achieved in 41% patients ( 41 ). In a quantitative analysis of novel “minimally invasive” approaches, the pooled seizure-free rate per person-year was 0.59 with LITT and 0.38 with RF-TC, which were not as efficacious as open surgery ( 42 ). Nevertheless, LITT and RF-TC remain surgical options, even as a first-line treatment for certain epilepsy indications, while more high-quality evidence is needed.…”
Section: Discussionmentioning
confidence: 99%